The combat path and command activity of Hero of the Soviet Union S. Nurmagambetov (Journal of history, 2024)
The article tells about the place of birth of Sagadat Nurmagambetov, his childhood, the loss of his parents at a young age, and his school education. It is examined how he was drafted into the ranks of the Red Army in 1942, studied at the 1st Turkestan Machine Gun School in the city of Kushka of Turkmenistan, in 1943 went to the western front line, and was appointed commander of a platoon of heavy machine guns of a 19-year-old lieutenant. It describes his participation in the battles of the Second World War to liberate the Krasnodar Territory, Ukraine, Moldova, Western Belarus, Poland and the Berlin operation. During the war, he repeatedly took part in military operations, for bravery in these battles, the history of obtaining the title of Hero of the Soviet Union is determined. After the end of the war, his achievements in various military districts are indicated. After the Republic of Kazakhstan gained independence, an examination of his appointment by Presidential Decree as the first Minister of Defense was carried out. Arguments are given about his role in creating a valiant army and improving the system of military personnel and military education. Military educational institutions named after him in the country are reported, books written about the front are shown, good deeds in the formation of traditions and strong foundations of the modern Armed Forces are described.Keywords: College, machine gunner, officer, front, courage, valor, hero, battle, war, army, defense, armed forces, personnel, military education.